Hypothalamic impairment underlying heat intolerance in pregnant mice. (15th July 2019) - Lin, Cheng-Hsien; Chen, Sheng-Hsien; Chang, Ching-Ping; Lin, Kao-Chang
Abstract: Pregnant women are vulnerable to heat stroke reactions caused by high environmental temperatures. Heat intolerance is associated with hypothalamic impairment. Here, we aim to ascertain whether pregnancy causes heat intolerance by inducing hypothalamic impairment in mice. In the heated groups, mice were exposed to whole body heating (WBH; 41.2 °C for 1 h) in an environment-controlled chamber. Then, they were returned to normal room temperature (26 °C) immediately after WBH. In the hyperbaric oxygen therapy (HBO2 T) groups, mice were exposed to 100% O2 at 2.0 atm absolute (ATA) for 4 h immediately post-WBH. Mice that survived after 4 h of WBH were considered survivors. Here, we show that when pregnant mice underwent non-HBO2 T (21% O2 at 1.0 ATA for 4 h) after WBH, the survival rate was 4/20, and the core temperature at 4 h post-WBH was 31.2 ± 0.2 °C. Both the survival rate and core temperature of HBO2 T pregnant mice (10/10 and 35.2 ± 0.3 °C, respectively) were significantly greater than those in non-HBO2 T pregnant mice. Compared to non-HBO2 T heated mice, the HBO2 T heated mice exhibited lower neurological severity scores, reduced hypothalamic neuronal damage, fewer apoptotic cells, reduced multiorgan damage scores, and lower hypothalamic levels of proinflammatory cytokines and nitrogen and oxygen radical species. Compared to non-HBO2 T heated mice, the HBO2 T-treated heated mice had significantly higher hypothalamic-pituitary-adrenal axis activity (evidenced by higher serum levels of both adrenocorticotrophic hormone and corticosterone). In conclusion, pregnancy induces heat intolerance by inducing hypothalamic impairment in mice. Additionally, HBO2 T protects against heat intolerance in pregnant mice by preserving hypothalamic integrity. Highlights: Pregnant women constitute the most at-risk population for heat stress. Hypothalamic impairment causes heat intolerance in pregnant mice. Hypothalamic dysfunction and heat intolerance can be prevented by hyperbaric oxygen treatment.